Description of Ease of Market Access, Access to Information, and Availability of Transmigrant Transportation in Doing Business in Banyuasin and Ogan Ilir Regencies, South Sumatra Province, Indonesia - Malta (GoAcademica Research & Publishing, 2021)
The success and sustainability of the transmigration program is largely determined by the quality of the supporting factors which are the main pillars of transmigration programs and activities, namely ease of market access, access to information, and availability of transportation. The purpose of this study was to describe the ease of market access, access to information, and the availability of transmigrant transportation in farming in the Districts of Banyuasin and Ogan Ilir, South Sumatra - Indonesia. The research was conducted from May 2016 to January 2017. The total population was 3,537 transmigrant families. The number of samples in this study was determined using the Slovin formula. This study involved 359 respondents who were determined by stratified random sampling. The research data consists of primary data and secondary data. Primary data were obtained through structured interviews, in-depth interviews and field observations. The results showed that ease of market access was moderate, information access was low, and transportation availability was low.